Product Development of Sneakers Design Based on Consumer Preference Through Integration of Kano Method and Quality Function Deployment - Devi Susiati; Lukmandono (UNIPA PRESS, 2022)
Ardiles brand shoes are local Indonesian brand shoes that have been around since 1950. Ardiles produces several shoe models, one of which is sneakers. This brand received the top brand award from 2018 to 2021. In analyzing consumer needs, this study uses the Kano method and Quality Function Deployment (QFD). The attributes used to find 25 attributes based on 8 dimensions of product quality. The results of the research using the Kano category method were found that there are 2 attributes in the attractive category, 3 in the indifferent category, 3 in the must be category, and 17 in the one-dimensional category. Furthermore, the results of the QFD method get the top 5 attributes, namely shoes have two functions/models (low cut and high cut) with a value of 20.50%, shoe products have a warranty with a value of 13.87%, safe foot protection with a value of 9, 56%, eco print batik motifs with a value of 9.31%, and non-slip soles with a value of 6.39%. Efforts to improve with HOQ analysis obtained 16 technical requirements attributes with 5 highest priority including upper material type with a contribution value of 18.83%, outsole material type with a contribution value of 18.24%, locking system with a contribution value of 14.58 %, additional features with a contribution value of 13.28%, and the type of locking material with a contribution value of 8.54%.